2014
DOI: 10.1371/journal.pone.0096630
|View full text |Cite
|
Sign up to set email alerts
|

TIMI Frame Count and Adverse Events in Women with No Obstructive Coronary Disease: A Pilot Study from the NHLBI-Sponsored Women's Ischemia Syndrome Evaluation (WISE)

Abstract: BackgroundTIMI frame count (TFC) predicts outcomes in patients with obstructive coronary artery disease (CAD); it remains unclear whether TFC predicts outcomes in patients without obstructive CAD.MethodsTFC was determined in a sample of women with no obstructive CAD enrolled in the Women's Ischemia Syndrome Evaluation (WISE) study. Because TFC is known to be higher in the left anterior descending artery (LAD), TFC determined in the LAD was divided by 1.7 to provide a corrected TFC (cTFC).ResultsA total of 298 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 26 publications
4
19
0
Order By: Relevance
“…Using the ISHLT grading criteria, patients with no or mild CAV had a higher MPRi compared to those with more significant CAV. Additionally, we confirmed the results of other smaller studies that showed that elevated TIMI frame counts correlated with microvascular disease in both native and transplanted hearts [3, 4345]. We also found that worsening in MPRi and GLS was associated with worsening in TIMI frame counts.…”
Section: Discussionsupporting
confidence: 91%
“…Using the ISHLT grading criteria, patients with no or mild CAV had a higher MPRi compared to those with more significant CAV. Additionally, we confirmed the results of other smaller studies that showed that elevated TIMI frame counts correlated with microvascular disease in both native and transplanted hearts [3, 4345]. We also found that worsening in MPRi and GLS was associated with worsening in TIMI frame counts.…”
Section: Discussionsupporting
confidence: 91%
“…Future studies should also address whether and to what extent sex differences in response to volume overload and biological and/or hormonal differences between the sexes might have contributed to the differential outcomes, including pulmonary vascular function, plaque characteristics, microvascular dysfunction, inflammation, and left atrial function. [37][38][39] Of note, the less frequent restoration of TIMI 3 flow in women compared to men in our study is consistent with a potential role for microvascular dysfunction contributing to the poor prognosis in women. 39 …”
Section: Discussionsupporting
confidence: 81%
“…[37][38][39] Of note, the less frequent restoration of TIMI 3 flow in women compared to men in our study is consistent with a potential role for microvascular dysfunction contributing to the poor prognosis in women. 39 …”
Section: Discussionsupporting
confidence: 81%
“…87 Although not visualized using angiography, the speed of contrast movement during angiography as the resting corrected Thrombolysis In Myocardial Infarction (cTIMI) frame count can be considered, and has been shown to correlate with aspects of CMD in WISE and other study participants. [92][93][94] For example, cTIMI scores in women with no obstructive CAD are predictive of hospitalizations for angina. 94 cTIMI has been used to show that the presence of flow delays immediately after thrombolysis is correlated with CMD.…”
Section: Noninvasive Testingmentioning
confidence: 99%
“…[92][93][94] For example, cTIMI scores in women with no obstructive CAD are predictive of hospitalizations for angina. 94 cTIMI has been used to show that the presence of flow delays immediately after thrombolysis is correlated with CMD. 92 This measure is objective, reproducible, and highly correlated with Doppler blood-flow measurements.…”
Section: Noninvasive Testingmentioning
confidence: 99%